Ergonomic Hazards and Musculoskeletal Disorders among Tea Farmers - Jesica Natalia Simanungkalit; Yovani Rehuel Br Sitepu (Global Health Science Group, 2020)
Tea farmers have the potential to experience a number of hazards in their workplace, from physical, biological, chemical, ergonomic and psychosocial factors. Ergonomic hazards are one of the potential hazards that are often experienced by tea gardeners. Musculoskeletal disorders are one of the most common health problems experienced by tea farmers. Ergonomic hazards and their relationship to musculoskeletal disorders are becoming a problem of increasing concern in agricultural production. The purpose of this article is to find out more about the dangers of ergonomics and musculoskeletal disorders in tea farmers. The research method used is literature review with literature searching sourced from the NCBI database, Elsevier, Agromedicine Journal and other national articles. Literature searching was carried out with the keywords ergonomic hazards, musculoskeletal disorders and tea farmers. The searching literature resulted in 782 articles published in the period 2008-2020 and then 26 articles were selected. The articles that have been selected and collected will then be analyzed using a systematic literature review, namely by systematically identifying, assessing, evaluating and interpreting all findings with a particular topic focus. The results of the analysis of this study indicate that the potential dangers of ergonomics to tea farmers are caused by physical loads and work attitudes away from nature. From several sources, it is stated that the dangers of ergonomics have the potential to provide musculoskletal disorders to tea farmers.